Notch1-MAPK signaling axis regulates CD133+ cancer stem cell-mediated melanoma growth and angiogenesis - Kumar, Dhiraj; Kumar, Santosh; Gorain, Mahadeo; Tomar, Deepti; Patil, Harshal S.; Radharani, Nalukurthi N. V.; Kumar, Totakura V. S.; Patil, Tushar V.; Thulasiram, Hirekodathakallu V.; Kundu, Gopal C. (Journal of Investigative Dermatology, 2016)
Functional characterization and understanding of the intricate signaling mechanisms in stem-like cells is crucial for the development of effective therapies in melanoma. We have studied whether melanoma cells are phenotypically distinct and hierarchically organized according to their tumorigenic nature. We report that melanoma-specific CD133(+) cancer stem cells exhibit increased tumor-initiating potential, tumor-endothelial cell interaction, and lung metastasis. These cells are able to transdifferentiate into an endothelial-like phenotype when cultured under endothelial differentiation-promoting conditions. Mechanistically, Notch1 upregulates mitogen-activated protein kinase activation through CD133, which ultimately controls vascular endothelial growth factor and matrix metalloproteinase expression in CD133(+) stem cells leading to melanoma growth, angiogenesis, and lung metastasis. Blockade or genetic ablation of Notch1 and mitogen-activated protein kinase pathways abolishes melanoma cell migration and angiogenesis. Chromatin immunoprecipitation and reporter assays revealed that Notch1 intracellular domain regulates CD133 expression at the transcriptional level. Andrographolide inhibits Notch1 intracellular domain expression, Notch1 intracellular domaindependent CD133-mediated mitogen-activated protein kinase and activator protein-1 activation, and epithelial to mesenchymal-specific gene expression, ultimately attenuating melanoma growth and lung metastasis. Human malignant melanoma specimen analyses revealed a strong correlation between Notch1 intracellular domain, CD133, and p-p38 mitogen-activated protein kinase expression and malignant melanoma progression. Thus, targeting Notch1 and its regulated signaling network may have potential therapeutic implications for the management of cancer stem cell-mediated melanoma progression.